Foreign Direct Investment and Forest Land: A Sectoral Investigation - Doytch, Nadia (Archīum Ateneo, 2024)
This is a study of the effects of sectoral FDI inflows on the rates of change of forest land and the ecological footprint of economic activity measured in forest land. We test the “FDI ecological halo” hypothesis (Doytch, 2020) for nine distinct sectoral FDI inflows, including agricultural FDI, mining FDI, manufacturing FDI, construction FDI, financial FDI, transport FDI, tourism FDI, communications FDI, and trade services FDI, in addition to total FDI, using a global sample of countries and a GMM econometric approach. We find that one percentage increase (% GDP) in agricultural FDI, mining FDI, manufacturing FDI, and construction FDI can reduce 2.87 %, 1.76 %, 0.19 %, and 1.28 % of forest land area, respectively, and all but manufacturing FDI, increase the forest land footprint from. At the same time, the results associated with services FDI are mixed: trade services FDI hurts the forest environment, while one percentage increase (% GDP) in communications FDI, financial FDI, and transport FDI can increase forest land area to 0.24 %, 0.02 %, and 3.02 %, respectively. In the case of tourism FDI, the results are mixed. The results suggest that FDI in sectors that are “closer to nature”, such as agriculture and mining are more prone to cause harm to forests and therefore need to be regulated with maximum stringency. Some services FDI, such as communications FDI and financial FDI could be stimulated without harm to the forest environment.